THE ROLE OF DISTRIBUTIVE JUSTICE COMPENSATION, COMMITMENT AND WORK DISCIPLINE TOWARDS WORK PERFORMANCE - Yusup; Suparno (Pedagogic Research-Applied Literacy Journal, 2024)
This research aims to analyze the influence of distributive justice compensation, commitment and work discipline towards employee work performance. The research method used is a quantitative method with a survey approach. Data was obtained through a questionnaire distributed to employees in CV. Nursa Prima Mojokerto. Data analysis was carried out using multiple linear regression to see the influence of the independent variables (distributive justice compensation, commitment and work discipline) on the dependent variable (work performance). The research results show that these three independent variables significantly increase work performance, both partially and simultaneously. These findings indicate that the company needs to pay attention to aspects of fairness in providing compensation, improve work discipline, and build employee commitment to improve work performance. It is hoped that this research can contribute to the development of effective human resource management strategies in the company.